2015
DOI: 10.3390/rs71114939
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Six Algorithms to Monitor Wheat Leaf Nitrogen Concentration

Abstract: Abstract:The rapid and non-destructive monitoring of the canopy leaf nitrogen concentration (LNC) in crops is important for precise nitrogen (N) management. Nowadays, there is an urgent need to identify next-generation bio-physical variable retrieval algorithms that can be incorporated into an operational processing chain for hyperspectral satellite missions. We assessed six retrieval algorithms for estimating LNC from canopy reflectance of winter wheat in eight field experiments. These experiments represented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 56 publications
6
70
0
Order By: Relevance
“…Consistent with the results of Xia Yao et al [4], our study revealed that the most informative feature wavelengths could vary in different growth stages and experimental conditions. Thus, further works need to be conducted in selecting and explaining new wavelengths for various experiments of LNC estimation, including different sites, experimental conditions and species.…”
Section: Band Combinations Based On Hsl Data For Rice Lnc Estimationsupporting
confidence: 80%
See 4 more Smart Citations
“…Consistent with the results of Xia Yao et al [4], our study revealed that the most informative feature wavelengths could vary in different growth stages and experimental conditions. Thus, further works need to be conducted in selecting and explaining new wavelengths for various experiments of LNC estimation, including different sites, experimental conditions and species.…”
Section: Band Combinations Based On Hsl Data For Rice Lnc Estimationsupporting
confidence: 80%
“…Thus, further works need to be conducted in selecting and explaining new wavelengths for various experiments of LNC estimation, including different sites, experimental conditions and species. Xia Yao et al [4] and Tian, Y.C. et al [48] revealed that LNC models exhibited better and more stable performances in later stages than at the early stages.…”
Section: Band Combinations Based On Hsl Data For Rice Lnc Estimationmentioning
confidence: 99%
See 3 more Smart Citations